(untitled) (Cadernos de Sociomuseologia, 2022)
: In view of Paulo Freire’s centennial this article was constructed with the aim of presenting contributions of Freirian pedagogy in the LGBTQI struggle for an anti-fascist and non-banking education, where the logic of oppression that interdicts the issues of this community in the production of knowledge intended by the school is no longer admitted. Thus, through the exploration of a memory of homophonic violence experienced in my teaching career as a teacher in high school classes in public basic education, I reflect on how the curriculum prescription system makes the production of a non-banking education unfeasible and interested in the immediate reality of the subjects of the pedagogical act, thus neglecting the production of a moral and ethical life in the sense of caring for the differences present in the school context. This produces a silencing in relation to gender and sexuality violence in pedagogical situations. On the occasion of this violence I was denounced to the police station under accusation of gender indoctrination, which supposedly deviated from what was prescribed in the sociology curriculum. The (auto)biography is then the methodological ground where the understandings present in this work are developed Keywords: Paulo Freire. LGBTQI. Anti-fascism.